SMS Based Exam Schedule Information Unit Link Using Data Protocol Method - Bahri, Saeful; Fadillah Rezky, Syarifah; Sinuraya, Junus (Bahasa Indonesia, 2021)
SMS from these various considerations is feasible to use. The level of ownership of cellular phones and affordable costs are considerations that support the adoption of this technology to be widely applied for the application of information system development in the present and in the future.Distance and long time are no longer a problem that can hinder obtaining information about the exam schedule, the SMS received does not come directly from the sender, but comes from the SMS Center. So, before the SMS reaches the recipient, the SMS actually enters the SMS Center first,The PDU contains not only the message, but also a lot of information about the sender. Starting from the sender's number, the sender's SMSC number, the validity time of the SMS, and so on. Everything is built in the form of hexadecimal numbers. SMS-based student exam scheduling using AT Command GSM which is used as a command in communication with the serial port. Scheduling with the AT command technique is very effective as information for students.